2010
DOI: 10.1111/j.1532-950x.2010.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications and Survival after Enterolith Removal from the Ascending or Descending Colon in Horses

Abstract: Incidence of postoperative complications and survival are not affected by the site of enterolith obstruction in the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
4
32
3
Order By: Relevance
“…Despite the reported difficulties associated with surgery involving the small colon, previous reports on short‐term survival have been favourable, with survival rates to hospital discharge ranging from 84–95% . This compares to 91% survival to discharge in horses that recovered following anaesthesia in the present study.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Despite the reported difficulties associated with surgery involving the small colon, previous reports on short‐term survival have been favourable, with survival rates to hospital discharge ranging from 84–95% . This compares to 91% survival to discharge in horses that recovered following anaesthesia in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Long‐term survival to 6 months post operatively has been reported to be 90 and 93% in 2 previous studies , with survival to one year reported at 75, 94 and 85%, respectively in 3 others . In the present study, 90.4% of horses discharged from the hospital were still alive one year post operatively.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Its prevalence varies widely depending on the location and pathology of the primary gastrointestinal lesion and on the geographical location of horses. Diarrhoea is usually defined as passage of unformed faeces for more than 24 h or on 2 or more consecutive occasions following surgical treatment of colic. However, in many studies, case definition is poorly described.…”
Section: Post Operative Diarrhoeamentioning
confidence: 99%
“…Horses diagnosed with large intestinal lesions were significantly more likely to develop diarrhoea post operatively compared with other intestinal lesions . Diarrhoea has been reported to be a frequent complication following surgical correction of strangulating large colon volvulus (28–45%) , treatment of sand impaction of the large colon (46%) and following removal of large colon enteroliths (20%) . Horses treated surgically for small colon diseases were shown in one study to be 17 times more likely to develop diarrhoea post operatively compared with other surgical lesions , with the prevalence of diarrhoea ranging from 11% to 70% .…”
Section: Post Operative Diarrhoeamentioning
confidence: 99%